Proceso para la importación de frascos de vidrio de 250cc para el envasado de mermelada desde Bogotá – Colombia hacia el Distrito Metropolitano de Quito de la provincia de Pichincha – Ecuador - Pozo Paredes, Karla Verónica (2013)
A process for glass bottles Import 250cc from Bogota - Colombia to Quito - Ecuador, is considered a hot topic for the industry and helps Ecuadorian National, you can analyze if covers 100% of the market need for both domestic consumption and for export. The 250cc glass bottles described in this study and used in the packaging of jams. This research will provide information on domestic production, product features, product usage, and actual product demand and explain the import process suitable for this product. This research provides guidance for the import of glass jars and detailed graphics, using any means necessary and optimizing resources, logistics options exist to optimize time and resources to obtain optimal merchandise packaging…